Study on event routing algorithms for publish/subscribe communication systems - XUE Xiao-ping 1; WANG Xiao-ping 2; ZHANG Si-dong1; ZHANG Hong-ke1 (Tongxin xuebao)
The architectures of publish/subscribe communication systems and various routing mechanisms and algorithms were discussed and reviewed,including the basic methods of finding communication objects,routes optimization and routes for supporting topology change and client mobile,etc; The routing methods of famous P/S systems were compared and analyzed; On the perspective of the system scalability,the direction of further research was proposed finally.